Current status of pig heart xenotransplantation. (November 2015) - Mohiuddin, Muhammad M.; Reichart, Bruno; Byrne, Guerard W.; McGregor, Christopher G.A.
Abstract: Significant progress in understanding and overcoming cardiac xenograft rejection using a clinically relevant large animal pig-to-baboon model has accelerated in recent years. This advancement is based on improved immune suppression, which attained more effective regulation of B lymphocytes and possibly newer donor genetics. These improvements have enhanced heterotopic cardiac xenograft survival from a few weeks to over 2 years, achieved intrathoracic heterotopic cardiac xenograft survival of 50 days and orthotopic survival of 57 days. This encouraging progress has rekindled interest in xenotransplantation research and refocused efforts on preclinical orthotopic cardiac xenotransplantation. Highlights: There has been significant improvement in long term pig-to-baboon heterotopic cardiac xenograft survival. Immune suppression using an anti-CD40 antibody appears to have improved xenograft survival. The value of further donor genetic modification remains to be proven. Experimental cardiac xenotransplantation is transitioning to preclinical life sustaining cardiac xenotransplantation studies.